EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) DENGAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL DITINJAU DARI KECERDASAN EMOSIONAL SISWA - Winata, Rahmat; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research aimed to find out: (1) Which one give better mathematicsâ learning achievement, learning model of NHT with CTL, TPS with CTL or direct learning, (2) Which one have better mathematicsâ learning achievement, students who have high, medium or low. (3) On each learning model, which one give better achievement on each emotional intelligence. (4) On each level of emotional intelligence, which one give better mathematicsâ learning achievement, learning model of NHT with CTL, TPS with CTL or direct learning. This research was the quasi-experimental research with 3Ã3 factorial design. The population of research was all students of Junior High School (SMP) in Karanganyar. The samples were 308 students; consist of 104 students in the first experimental class, 104 in the second experimental class, and 100 students in control class. The technique of analyzing the data was two-ways ANOVA with unbalanced cells. The result of research showed as follows. (1) The NHT with CTL given learning achievement as good as the TPS with CTL. NHT and TPS with CTL provided better learning achievement than the direct learning, (2) The students with high emotional intelligence had better learning achievement than those with medium and low emotional intelligence. The students with medium emotional intelligence had better learning achievement than did those with low emotional intelligence, (3) Students taught by using NHT and TPS with CTL, students with high emotional intelligence had learning achievement as good as the medium emotional intelligence. The students with high emotional intelligence had better learning achievement than the students with low emotional intelligence. The students with medium emotional intelligence had learning achievement as good as the students with low emotional intelligence. Students taught by using direct learning had equal learning achievement in each level of emotional intelligence, (4) Students with high emotional intelligence taught by using the NHT with CTL had learning achievement as good as the TPS with CTL. Students with high emotional intelligence taught by using the NHT and TPS with CTL had better learning achievement than the direct learning. Students with medium and low emotional intelligence had equal learning achievement in each learning model.Keywords: NHT with CTL, TPS with CTL, learning achievement, emotional intelligence.